1980
DOI: 10.4319/lo.1980.25.2.0290
|View full text |Cite
|
Sign up to set email alerts
|

Sterols in decomposing Spartina alterniflora and the use of ergosterol in estimating the contribution of fungi to detrital nitrogen1

Abstract: Changes in concentrations of free sterols in decomposing Spartina alterniflora indicate that this marsh grass may be a significant source of sterols, primarily sitosterol, to tidal waters. These tidal waters may then transport the sterols (adsorbed to particulate matter) to nearby coastal sediments. Estimates of bacterial and fungal biomass in the detritus show that the living cells of these microbes account for only a minor part of the relative increase in nitrogen observed during decomposition. Biomass was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
2
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 21 publications
7
44
2
2
Order By: Relevance
“…Probably the increasing fungal biomass had an inhibitory effect on bacterial growth. Some previous studies on microbial colonization of plant detritus in aquatic environments have shown that fungi are primary colonizers whereas bacteria are secondary colonizers (Suberkropp et al 1976;Lee et al 1980), although in other studies, bacteria were the first colonizers, as in the present study (Newell 1981;Szabó et al 2003;Ágoston-Szabó & Dinka 2005).…”
Section: Microbiological Parameterscontrasting
confidence: 51%
“…Probably the increasing fungal biomass had an inhibitory effect on bacterial growth. Some previous studies on microbial colonization of plant detritus in aquatic environments have shown that fungi are primary colonizers whereas bacteria are secondary colonizers (Suberkropp et al 1976;Lee et al 1980), although in other studies, bacteria were the first colonizers, as in the present study (Newell 1981;Szabó et al 2003;Ágoston-Szabó & Dinka 2005).…”
Section: Microbiological Parameterscontrasting
confidence: 51%
“…The accumulation of nitrogen in litter has been observed frequently during decay (Odum et al 1973, Rice & Tenore 1981, Melillo et al 1982 litter (Suberkropp et al 1976, Odum et al 1979) and have suggested that microbial and fungal biomass account for less than 20 % of the nitrogen present in decaying litter of Spartina alterniflora (Rublee et al 1978, Lee et al 1980, Marinucci 1982, Hicks 1983). Fungi contributed the major portion of microbial nitrogen in Spartina litter (Lee et al 1980, Newel1 & Hicks 1982, Marinucci et al 1983).…”
Section: Relation Of Nitrogen and Lignin Contents To Decay Ratementioning
confidence: 99%
“…l), during which 20 to 40 % of the original amount of material was removed. This initial stage presumably involved leaching of soluble organic materials (Nykvist 1959, Odum & Heywood 1978, Haines & Hanson 1979, Lee et al 1980, Montagna & Ruber 1980.…”
Section: Total Weight Lossmentioning
confidence: 99%
“…The first phase is leaching of soluble organic matter within days, followed by the second stage of months with the biopolymers degraded and soluble organic substances released by the action of microorganisms. The third phase can take longer (years) than the first two phases, during which cellulose and lignin and other refractory organic compounds are remained [34][35][36][37]. Chen and Jiang have reported that bacteria activities played the most important roles in the late stage of plant degradation [38].…”
Section: Leaching Of Doc and Dnmentioning
confidence: 99%